Carbohydrate Content in the GDM Diet: Two Views: View 2: Low-Carbohydrate Diets Should Remain the Initial Therapy for Gestational Diabetes - Mulla, Wadia R. (Diabetes Spectr, 2016)
IN BRIEF The appropriate dietary intervention for gestational diabetes mellitus (GDM) is not clear. Traditionally, a low-carbohydrate diet has been prescribed. Recently, there has been a movement to prescribe a diet higher in nutrient-dense carbohydrate as the initial treatment for GDM. At this time, there is insufficient outcome data to support this type of diet.